Symptom Evaluation in Pediatric Oncology Outpatient Setting; A Cross-Sectional Study: Symptoms in Pediatric Oncology - Kargar, Mona; Motaghedi, Rozita; Mansouri, Ava; Hadjibabaie, Molouk; Heidari, Kazem; Rashidian, Arash; Ansari, Shahla; Gholami, Kheirollah (Iranian Journal of Pharmaceutical Sciences, 2019)
Detection and management of cancer-related symptoms is a key component in children‟s quality of life. We evaluate symptoms and their severity in Iranian pediatric oncology outpatients using Therapy-Related Symptom Checklist for Children (TRSC-C). This was a cross-sectional study conducted in two outpatient pediatric oncology settings. We included all patients aged between 5-17 years. The validated and reliable Persian translated version of TRSC-C was used to study the symptoms. Overall 1425 symptoms were documented from 162 patients (mean age 8.6 ±3.2, acute lymphoblastic leukemia: 76.5%). In 96.3% of patients at least one symptom was present. Twenty (12.34%) patients experienced at least 15 events. Irritable, loss of appetite, cough, pain and hair loss were the top 5 frequent symptoms. The highest mean severity scores were also belonged to irritable, loss of appetite, and hair loss. We found no significant difference between gender, age group or time of the last chemotherapy with mean total severity scores or total number of symptoms (P>0.05). In conclusion, TRSC-C is an appropriate symptom assessment checklist for our settings and it would give us the ability to track symptoms and designate clinical interventions based on the frequent and severe identified symptoms.